Thermochemical liquefaction of wheat straw and its effectiveness as an extender for asphalt binders: Characterization of liquefied products and potential opportunities. (25th October 2021) - Jiang, Xiuming; Li, Peilong; Ding, Zhan; Wang, Aibo; Bing, Hui; Zhang, Jing
Highlights: Liquefied products of wheat straw have similarities to petroleum-based asphalt. Physicochemical properties of liquefied products are influenced by solvent types. Improved high/low-temperature performances are found in bio-asphalt binders. Liquefied products deepen the non-Newtonian flow behavior of bio-asphalt binders. The fusion of liquefied products and the neat asphalt binder is probably physical. Abstract: Numerous attempts have been carried out to develop potential substitutes for petroleum asphalt binders from various biomass resources. This research aims to investigate the effectiveness of partially replacing asphalt binders with thermochemical liquefied products (LPs) of wheat straw. The LPs were obtained by acid-catalyzed liquefaction in organic solvents, based on which nine kinds of bio-asphalt binders distinguished by the type and content of LPs were prepared by mechanical stirring. To evaluate the physicochemical properties of the LPs, the Fourier transform infrared (FTIR) spectroscopy test, gel permeation chromatography (GPC) test, thermogravimetric (TG) test and rotational viscosity (RV) test were conducted. The potential advantages of bio-asphalt binders were explored by the RV test, dynamic shear rheometer (DSR) test, scanning electronic microscopy (SEM) test and FTIR test. The results demonstrate that LPs consist of 79%–88% bio-oils with low molecular weight and a small amount of solid residues. Compared with asphalt binders, more polar groups (e.g. hydroxyl, carbonyl and alcohol, etc.) with low boiling points are found in LPs, resulting in a lower volatilization and degradation temperature. There is a high chance for the fusion of LPs and asphalt binders to be physical integration. Further, the non-Newtonian flow behavior of asphalt binders is deepened by LPs. Nevertheless, better low-temperature cracking resistance and high-temperature performance are found from different types of bio-asphalt binders. It should be noted that the relationship between performances of bio-asphalt binders and the content of LPs needs more attention in further researches.